Tool path planning in flank milling based on dual spherical spline - Zhou, Yayun; Schulze, Jörg; Schäffler, Stefan (GRAPP 2011 - Proceedings of the International Conference on Computer Graphics Theory and Applications, 2011)
The flank milling (side milling) method, which uses the manufacturing tool side to remove material, is widely used in industry to manufacture ruled surfaces. Ruled surfaces are often used in blade design considering the aerodynamics requirements and the manufacture cost. A common way to derive a flank millable blade surface is to adopt a certain ruled surface approximation algorithm before the surface is delivered to the manufacturer. In this paper, a new tool path planning approach is proposed based on the offset theory and the kinematic ruled surface approximation. The novelty of this approach is to denote the drive surface as a dual spherical spline, which is a new ruled surface representation. This drive surface is derived by kinematically approximating the offset surface of the original design as a ruled surface. Therefore, the designed blade surface is represented as a flank milling tool path with a cylindrical cutter in CNC machining. This approach delivers more accuracy compared with convectional tool position optimization methods. By integrating the manufacture requirements into the design phase, this approach also reduces the developing cycle time and the manufacturing cost.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Blade design; Dual spherical spline; Flank milling; Ruled surface